Asthma and Injury Risk: A Large Scale Population-Based Study - Liang, Wenbin; Chikritzhs, Tanya (Scientific Research Publishing, 2012)
Purpose: Clinical data suggest that asthma impairs sleep quality and further impairs cognitive performance during the daytime, while there is a causal relationship between impaired sleep quality and injuries. Therefore asthma patients may have increased risk of injury, and this is supported by our recent population-based studies conducted in Australia. This study is to investigate the effect of asthma on the risk of injury at the population level using data from the U.S. National Health Interview Survey collected in 2008, 2009, and 2010. Method: Data from the 2008, 2009 and 2010 National Health Interview Surveys were combined and analyzed together. Results: U.S. adults with current or previous asthma had significantly greater risk of injury compared to those without asthma. The risk of injury was also significantly higher among children with current asthma. Conclusion: This population-based study provided further evidence on the positive association between asthma and risk of injury among both adults and children. The increased risk of injury among asthma patients is at least partly due to impaired sleep quality and quantity caused by asthma symptoms and asthma medications.